Chondroitin Sulfate-Based Imatinib Nanoparticles Targeting Activated Hepatic Stellate Cells Against Hepatic Fibrosis - Xunzhi Liu; Changlong Fang; Hongling Yu; Lu Huang; Jiaxing Feng; Shiqin Luo; Li Song; Mengying Wu; Yulu Tan; Jianxia Dong; Tao Gong; Peihong Xiao (Pharmaceutics)
Background: Activated hepatic stellate cells (aHSCs) play a significant role during the onset of hepatic fibrosis, ultimately leading to excessive deposition of extracellular matrix (ECM) and other typical pathological features, and thus have become a popular target for the treatment of hepatic fibrosis. However, current aHSC-centric therapy strategies achieve unsatisfactory results, mainly due to the lack of approved anti-fibrosis drugs and sufficiently efficient aHSC-targeted delivery systems. In this study, our aim was to develop an Imatinib-loaded nanoparticle delivery system based on a chondroitin sulfate derivative to enhance aHSC targeting efficiency, improve the therapeutic effect for hepatic fibrosis, and investigate the underlying mechanism. Methods: The carboxyl group of chondroitin sulfate and the amino group of 1-hexadecylamine were linked by an amide bond in this study to produce the amphiphilic carrier CS-HDA. Then, the Imatinib-loaded nanoparticles (IM-CS NPs) were designed to efficiently target aHSCs through CD44-mediated endocytosis and effectively inhibit HSC overactivation via PDGF and TGF-β signaling pathways. Results: Both in vitro cellular uptake experiments and in vivo distribution experiments demonstrated that CS-HDA-modified nanoparticles (IM-CS NPs) exhibited a better targeting ability for aHSCs, which were subsequently utilized to treat carbon tetrachloride-induced hepatic fibrosis mouse models. Finally, significant fibrosis resolution was observed in the carbon tetrachloride-induced hepatic fibrosis mouse models after tail vein injection of the IM-CS NPs, along with their outstanding biocompatibility and biological safety. Conclusions: IM-loaded NPs based on an amphiphilic CS derivative have remarkable antifibrotic effects, providing a promising avenue for the clinical treatment of advanced hepatic fibrosis.